I Am Not Captain Dunsel! A (Former) Head of an Academic Branch Library Replies to Steven Bell. - Susanne J. Redalje (Issues in Science and Technology Librarianship)
In response to a 2009 LJ Newswire article by Steven Bell, the author discusses the aspects of closing special academic libraries as a new trend, and whether or not that trend is a good one. Also investigated are the reasons why there are specialty libraries, the need of students for such facilities and the consolidation and merger trends.